Energy Issues as an Influence Factor in the Moro Conflict in Southern Philippines - Musdalifah, Musdalifah; Sagena, Uni W. (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
This study discusses the crucial role of energy security factors in the protracted conflict between the Moro Muslim groups and the Philippine government. The primary reason for conducting this research is to provide a more comprehensive understanding of the strategic dimension of natural resources, particularly energy, which is often overlooked in conflict analyses that focus on political, social, religious, and cultural aspects. This research employs energy security theory as an analytical lens to examine how issues such as land grabbing and competition for control over natural resources in Mindanao contribute to the escalation or potential resolution of the conflict. Furthermore, this study identifies specific energy-related factors that exacerbate tensions, including resource competition, the economic impact of the conflict on the energy sector, and the role of international actors. Utilizing a qualitative approach and descriptive analysis methods through case studies and secondary data from various credible sources such as the official websites of BARMM, PIDS, and PSA, this research is expected to make a significant contribution to the field of International Relations by highlighting the interconnectedness between energy security and armed conflict. The findings of this study have the potential to enrich the theoretical understanding of how energy dynamics shape the conflict landscape and inform the development of more effective strategies for achieving energy stability and peace in conflict-affected regions. Keywords: energy, Mindanao, Moro conflict, Philippines Government